Optimal control of three-phase embedded power grids - Formentini, Andrea; Dewar, David; Zanchetta, Pericle; Wheeler, Patrick; Boroyevich, Dushan; Schanen, Jean-Luc (2016)
This paper presents an automated and scalable approach for the tuning of power converters control systems in embedded power grids. These are composed by different power converter interconnected to each other and are increasingly adopted in a range of applications among which micro-grids and more electric aircrafts. The interaction between the grid components may lead to instability, especially in presence of small passive filters. A structured state feedback optimal control approach is proposed to jointly design all power converters controllers in a coordinated way to maximize the performance of the grid and avoid instability due to converters interaction